2021
DOI: 10.3390/joitmc7010007
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness Improvement in Manufacturing Industry; Trilogy Study and Open Innovation Dynamics

Abstract: The purpose of this investigation is to compute overall equipment effectiveness (OEE) in the small-scale industry. The novel approach is introduced to detect bottlenecks by which OEE can be improved. This study attempts to help small-medium enterprises in analyzing performance in a better way. The automotive industry was chosen for conducting the research. The present study is comprised of three phases. In the first phase, OEE was computed and compared with world-class manufacturing. The second phase included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…These techniques were developed as tools of the lean approach. The literature review proves that the lean manufacturing approach has positively impacted production performance by eliminating sources of non-value-added activity, and it also reduces inventories and lead time [56,57].…”
Section: Literature Reviewmentioning
confidence: 94%
“…These techniques were developed as tools of the lean approach. The literature review proves that the lean manufacturing approach has positively impacted production performance by eliminating sources of non-value-added activity, and it also reduces inventories and lead time [56,57].…”
Section: Literature Reviewmentioning
confidence: 94%
“…Organizations of all types and sizes face internal and external factors and impacts, which cause uncertainty. The goals of an enterprise may cover various aspects of its activities: from the strategy to the production of goods (Siferd and Smeltzer 1998;Tayal et al 2021), to process (Shojaei and Haeri 2019;Syreyshchikova et al 2020a) and project development (Verma and Sinha 2020). The influence of uncertainty on an organization's goals is a risk, in essence.…”
Section: Introductionmentioning
confidence: 99%
“…Table 8 shows the actions taken to improve the shop floor, while Table 9 shows the list of requirements for the different processes of the shop floor. By inspecting the production on the shop floor and analyzing the information gathered from many sources, it was found that some of the activities and processes involved in production are the cause of high PT, which need to be eliminated [47][48][49][50][51]. Table 8 shows the actions taken to improve the shop floor, while Table 9 shows the list of requirements for the different processes of the shop floor.…”
Section: Resultsmentioning
confidence: 99%